On the Effect of the Key-Expansion Algorithm in Simon-like Ciphers. (5th July 2021) - Lu, Jinyu; Liu, Yunwen; Ashur, Tomer; Li, Chao
Abstract: In this work, we investigate how the choice of the key-expansion algorithm and its interaction with the round function affect the resistance of Simon-like ciphers against rotational-XOR cryptanalysis. We observe that, among the key-expansion algorithms we consider, Simon is most resistant, while Simeck is much less so. Implications on lightweight ciphers design are discussed and open questions are proposed.